PENGARUH PENGAWASAN, KOMITMEN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI & UMKM PROVINSI SUMATERA BARAT - Chientya Annisa Rahman Putrie (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
The purpose of the research is to reveal the influence of supervision, commitment and discipline to employee perfomance. Sample of the research have 46 employees of the Cooperative Department and UMKM in West Sumatera Province, with applied a stratified random sampling method. Data were collected by a questionnaire and analyzed with path analysis. Results of the analysis proves that supervision has positive and significant influence to work discipline. Influence of the commitment is positive and significant to work discipline. Influence of supervision is positive and significant to perfomance of employee. Influence of the commitment is positive and significant to perfomance employee and work discipline, that positive and significant impact to perfomance of Cooperative Dapartment and UMKM in West Sumatera Province.